KRITIK SASTRA TERHADAP PERANG SEBAGAI TRADISI DALAM CERPEN AMA TOBI KONFLIK BATAS KAMPUNG KARYA SILVESTER PETARA HURIT (SOSIOLOGI SASTRA MARXISME) - Yoakim Yolanda Mario Leu; Carlos Konda T Masan (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
Literary criticism functions scientifically to dissect the values ​​and moral messages in works through in-depth reading in order to understand the social reality depicted by the author. The focus of the problem in this research is to criticize the view of war as a tradition in the short story Ama Tobi: Conflict of Village Boundaries by Silvester Petara Hurit using the perspective of Marxist literary sociology. The important steps or stages of the research were carried out through qualitative descriptive procedures with content analysis techniques on data in the form of narratives and dialogues between characters who represent the economic basis and superstructure of society. The research findings reveal that the phenomenon of civil war in the Lamaholot region actually arose from the occupation and economic control of the colonialists who implemented divide and rule politics for capitalist profit. The attitude of considering violence as a noble tradition is considered a cultural arrogance that is very counterproductive because it ignores human rights. Empirically, the practice of physical warfare has been proven to only cause collective trauma, resentment between clans that is difficult to break, and social divisions that are detrimental to the order of living together. The main conclusion emphasizes that war is not an effective solution in resolving modern agrarian conflicts. The best legacy of tradition should be restored to community-strengthening values ​​such as deliberation and consensus, mutual cooperation, respect for ancestors, and peaceful dispute resolution mechanisms to achieve sustainable social harmony for all levels of Indonesian society, leading to greater prosperity.